Wnt-Signaling-Mediated Antiosteoporotic Activity of Porcine Placenta Hydrolysates in Ovariectomized Rats - Byoung-Seob Ko (Evidence-Based Complementary and Alternative Medicine, 2012)
Anti-osteoporotic effects of two types of porcine placenta hydrolysates (PPH) were evaluated in ovariectomized (OVX) rats orally administered PPH without (WPPH) or with (NPPH) ovarian hormones (1 g/kg bw/day). PPH groups were compared with OVX rats with estrogen replacement (0.1 mg/kg bw conjugated estrogen; EST), or dextrose (placebo; OVX-control) All rats received high-fat/calcium-deficient diets for 12 weeks. NPPH contained less estrogen and progesterone, but more essential amino acids, whereas the opposite was true for WPPH. NPPH decreased body weight and peri-uterine fat pads, and maintained uterus weight. NPPH rats had higher femur and lumbar spine bone mass density compared to controls; but less than those of EST rats. Serum phosphorus and urinary calcium and phosphorus levels were reduced in NPPH rats compared to OVX-controls. Serum bone-specific alkaline phosphatase, osteocalcin, and bone turnover marker levels were reduced NPPH rats compared to OVX-controls. WPPH produced results similar to those of NPPH, but less significant. Both NPPH and estrogen upregulated low-density lipoprotein receptor-related protein 5 and β-catenin in OVX rats, while the expression of dickkopf-related protein 1 was suppressed. In conclusion, NPPH exerted anti-osteoporotic effects by activating osteogenesis and stimulating Wnt signaling, possibly mediated by the various amino acids and not ovarian hormones.